Trace elements-induced phytohormesis: A critical review and mechanistic interpretation. Issue 19 (1st October 2020) - Shahid, Muhammad; Niazi, Nabeel Khan; Rinklebe, Jörg; Bundschuh, Jochen; Dumat, Camille; Pinelli, Eric
Abstract: Despite considerable research about biogeochemical behavior of trace elements (TEs) in soil-plant-human systems, there is still a gap of knowledge regarding dose–response relationship, especially for low-applied doses. Trace elements such as mercury, cadmium, antimony and others are highly toxic, without any known essential function in plants. Nevertheless, recent toxicology and risk assessment studies revealed TE-induced hormesis in plants, i.e. stimulation in plant growth at low-doses while suppression at high-doses. This is the first review critically reviewing the TE-induced phytohormetic. The review compares hormetic effects for 366 observations from various research articles among different (i) toxic TEs, (ii) plant species, (iii) plant response parameters (end points), and (iv) exposure durations. It was observed that various toxic TEs, especially Cd, induce hormesis in plants. The mean value of Maximum Stimulatory Response (MAX) was 27% higher compared to the control response, with a range of 0.71 to 1122%. This review critically highlights the TE-induced phytohormesis by discussing possible mechanisms such as the (i) activation of plant tolerance mechanisms after TE-induced overproduction of reactive oxygen species (ROS), and (ii) interplay between phytohormones and TE-mediated ROS production towards plant growth. Highlights: First review highlighting trace elements-induced hormesis in plants Trace elements -induced phytohormesis is evaluated for 366 endpoints The hormesis varies for different plants, trace elements, endpoints & durations Activation of plant defense and phytohormones results trace elements-induced hormesis Validation of mechanisms of trace elements-mediated phytohormesis is required Graphical Abstract: UF0001